Amygdalin as a chemoprotective agent in co-treatment with cisplatin - Panayiota Christodoulou; Panayiota Christodoulou; Panagiotis Boutsikos; Christiana M. Neophytou; Theodora-Christina Kyriakou; Theodora-Christina Kyriakou; Maria-Ioanna Christodoulou; Panagiotis Papageorgis; Anastasis Stephanou; Ioannis Patrikios (Frontiers Media S.A., 2022)
Amygdalin is a naturally occurring glycoside used in traditional Chinese medicine and is known to have anti-cancer properties. Even though the anti-cancer properties of amygdalin are well known, its effect on normal cells has not been thoroughly investigated. The aim of the present study was to investigate a possible chemo-protective role of amygdalin against the cytotoxic effects of chemotherapy for normal human cells. Specifically, it was tested in combination with a strong chemotherapeutic drug cisplatin. Human non-tumorigenic MCF12F epithelial cell line, human fibroblasts cells, human breast cancer MCF7 and MDA-MB-231 cells were treated with cisplatin in a dose- and time-depended manner in the absence or presence of amygdalin. When MCF12F cells and fibroblasts underwent pre-treatment with amygdalin followed by cisplatin treatment (24 h amygdalin + 24 h cisplatin), the cell viability was increased (22%, p < 0.001) as indicated using MTT assay. As attested by flow cytometry, combination treatment was associated with decreased the percentage of late apoptotic cells compared with monotherapy (fold-change of decrease = 1.6 and 4.5 for 15 and 20 μΜ, respectively). Also, the proteins expression of PUMA, p53, phospho-p53 and Bax decreased, when a combination treatment was used vs. cisplatin alone, while the proapoptotic proteins Bcl-2 and Bcl-xL exhibited an increased tendency in the presence of amygdalin. Moreover, the levels of pro-apoptotic genes PUMA, p53, and BAX mRNA were significantly downregulated (∼83%, ∼66%, and ∼44%, respectively) vs. cisplatin alone, while the mRNA levels of anti-apoptotic genes BCl-2 and Bcl-XL were upregulated (∼44.5% and ∼51%, respectively), vs. cisplatin alone after 24 h of combination treatment. The study on the Combination index (CI) assay indicated that amygdalin could be possibly considered as an antagonist to cisplatin (2.2 and 2.3) for MCF12F and fibroblast cells, respectively. In contrast, for the breast cancer MCF7 and MDA-MB-231 cells, amygdalin and cisplatin indicated a synergistic effect (0.8 and 0.65), respectively. Our present findings suggest that amygdalin has chemo-modulatory effect when used in co-treatment with cisplatin and is able to protect normal breast cells as well as the fibroblasts during chemotherapy treatment, indicating a strong selective chemoprotective ability and may contribute to a better quality of life for cancer patients.